Analisis Kepemimpinan, Manajemen Dan Struktur Organisasi Untuk Efektivitas Pelayanan Masyarakat Di Desa Sonobekel Kecamatan Tanjunganom Kabupaten Nganjuk - Wahyu Susanti; Dyan Arintowati (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
The purpose of this study was to analyze leadership, management and organization for the effectiveness of community services in Sonobekel Village, Tanjunganom District, Nganjuk Regency. Data collection techniques are used by conducting interviews and distributing questionnaires to village groups and staff. The sampling method used in this study uses Purposive Sampling. The population in this study was the Community of Sonobekel Village, Tanjunganom Subdistrict, Nganjuk Regency. While the sample in this study were 15 respondents. Then an analysis of the data obtained using quantitative analysis was carried out. Quantitative analysis is an interpretation of the data obtained in the study as well as the results of data processing that has been done by giving information and explanation. The results of data analysis concluded that Leadership, Management and Organizational Structure had a significant or partial effect on the Effectiveness of Community Services in Sonobekel Village, Tanjunganom District, Nganjuk Regency.